Flexible design principles: Street furniture design for transforming environments, diverse users, changing needs and dynamic interactions. Issue 9 (6th July 2015) - Siu, Kin Wai Michael; Wong, Kwun Sing Leo
Abstract : Purpose: – This paper aims to propose a set of flexible design principles for enhancing the flexibility of street furniture to deal with the diverse and changing urban environment. Flexibility is an important but less considered element of public design (otherwise called public environment and facility design), especially in regard to the street furniture that is encountered in everyday life. Taking Hong Kong as a case study, this paper gives an overview of the concepts of flexibility and flexible design, and identifies the current limitations and problems of the current street furniture design practices with respect to the diverse and changing urban environment. Design/methodology/approach: – Based on a review of the current literature and relevant documentation, interviews with government officers and different groups of users (including those with special needs), and field observations in Hong Kong's urban areas over a period of four years, the policies relating to street furniture design in Hong Kong and its management and implementation were evaluated. Findings: – The results indicate that the current street furniture in Hong Kong is unable to adapt to or resist changes, can easily cause safety and management problems and is not adaptable to new developments. This paper proposes six principles for the flexible design of street furniture, namely, custom in use, multifunctional use, responds effectively to changing circumstances, easily and conveniently managed, universal in use and sustainable in use. Research limitations/implications: – It is difficult to understand the diverse needs and preferences of different users in urban environments. The findings in this paper are based on intensive field work and broad industry experience. To deal with the rapid and ongoing urban change, this paper recommends a further long-term and in-depth study of street furniture. Practical implications: – Based on the findings, this paper proposes six flexible design principles for designing street furniture that is sufficiently flexible to meet the rapid and ongoing urban change and diverse users' needs. Social implications: – Different societies and urban areas faced different types and levels of changes. Therefore, a flexible approach to street furniture design is important and necessary. Originality/value: – The findings of this paper and the proposed six flexible design principles can provide insight and direction for government officials, design and planning professionals, developers, utility and management companies and communities on how to embed public design (i.e. policy, implementation and management) in the future.